2019
DOI: 10.1093/sleep/zsz139
|View full text |Cite
|
Sign up to set email alerts
|

Delayed sleep-onset and biological age: late sleep-onset is associated with shorter telomere length

Abstract: Study Objectives We evaluated the relationship between leukocyte telomere length (LTL) and sleep duration, insomnia symptoms, and circadian rhythm, to test whether sleep and chronobiological dysregulations are associated with cellular aging. Methods Data from the Netherlands Study of Depression and Anxiety (N = 2,936) were used at two waves 6 years apart, to measure LTL. Telomeres shorten during the life span and are importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 102 publications
0
19
1
Order By: Relevance
“…In this systematic review, we analyzed 11 articles on the association between TL and sleep ( Table 6 ) [ 43 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. In comparison with the other considered lifestyle factors in this review (PA and tobacco smoking), very few studies focused on sleep.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this systematic review, we analyzed 11 articles on the association between TL and sleep ( Table 6 ) [ 43 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. In comparison with the other considered lifestyle factors in this review (PA and tobacco smoking), very few studies focused on sleep.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, data from the intervention study only analyzed associations between sleep and TL cross-sectionally at baseline [ 132 ]. Only one study [ 135 ] had longitudinal data. Ten articles measured TL using PCR and 1/11 used southern blot [ 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to consider that factors in addition to brain injury may influence telomere length. Aging, 14 stress, 33 a history of smoking, 34 alcohol consumption, 35 and poor sleep 36 have been associated with shortened telomeres, whereas exercise may attenuate these deficits. 37 In this study, the Australian footballer and control groups were comparable with respect to the other potential modifying factors that were measured (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that women have at least a 40% increased risk of insomnia compared with men (Guidozzi, 2015). Gender differences in associations between sleep and LTL have not been investigated in any populations although associations between sleep duration, snoring or circadian rhythm disturbance, and LTL were reported (Barceló et al, 2010;Carroll et al, 2016;Shin et al, 2016;Wynchank et al, 2019). Our study showed that sleep quality was associated with LTL in female patients but not in male patients.…”
Section: Discussioncontrasting
confidence: 54%